Evaluating telemedicine diabetes mellitus: a mobile health app for type-2 diabetes - Muhammad Zakwan Abdul Karim; Norashikin M. Thamrin; Ruhizan Liza Ahmad Shauri; Rozita Jailani; Mohd Haidzir Abd Manaf; Nurul Amirah Mustapa (Institute of Advanced Engineering and Science, 2024)
Telemedicine diabetes mellitus (Tele-DM) mobile health (mHealth) tool functionality, usefulness, and user feedback were examined in this study. Data from nine distinct users of type-2 diabetes (T2D) patients, healthcare professionals (HCPs), and administrators was analyzed to determine functionality. Data retrieval times increased with database user data amount, according to the study. A 3-month program with five T2D patients reduced weight (0.98 kg) and Hemoglobin A1c (HbA1c) (0.34%). This shows that Tele-DM helps manage diabetes, but more participants are needed to confirm. Nine Tele-DM customers were satisfied with the app's reception, according to 14 online questionnaires. Overall, Tele-DM simplifies diabetic self-management in a novel way. This study shows its potential to transform diabetes management and address major healthcare issues.